2015
DOI: 10.1016/j.chembiol.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule Inhibitor of ATPase Activity of HSP70 Induces Apoptosis and Has Antitumor Activities

Abstract: The heat shock protein HSP70 plays antiapoptotic and oncogenic roles, and thus its inhibition has been recognized as a potential avenue for anticancer therapy. Here we describe the small molecule, apoptozole (Az), which inhibits the ATPase activity of HSP70 by binding to its ATPase domain and, as a result, induces an array of apoptotic phenotypes in cancer cells. Affinity chromatography provides evidence that Az binds HSP70 but not other types of heat shock proteins including HSP40, HSP60, and HSP90. We also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 55 publications
5
65
0
Order By: Relevance
“…This group found that Az induced cancer cell death by inhibiting HSP-70 and activating caspase dependent apoptosis [26]. Functionally, HSP-70 transports TFAM a major stimulator of mitochondrial activity and is found upregulated in cancer cells.…”
Section: Mitochondrial Transcription Factor a (Tfam)mentioning
confidence: 99%
“…This group found that Az induced cancer cell death by inhibiting HSP-70 and activating caspase dependent apoptosis [26]. Functionally, HSP-70 transports TFAM a major stimulator of mitochondrial activity and is found upregulated in cancer cells.…”
Section: Mitochondrial Transcription Factor a (Tfam)mentioning
confidence: 99%
“…A solid-support immobilized apoptozole was used to pinpoint HSP70 as the potential target of apoptozole in cells; the full-length protein and the ATPase domain bound to the resin, but the SBD did not. Mechanistic studies showed that apoptozole blocks the interaction of HSP70 with APAF-1 (apoptotic peptidase activating factor 1) without interfering with its binding to ASK1 (apoptosis signal-regulating kinase 1), JNK (c-Jun N-terminal kinase), BAX and AIF (apoptosis-inducing factor) (Ko et al, 2015). It restored the chloride channel activity of mutant cystic fibrosis transmembrane conductance regulator (CFTR) by promoting its membrane trafficking, suggesting its potential use, when utilized in concert with complementary methods, as a tool to dissect disease mechanism associated with cystic fibrosis (Cho et al, 2011).…”
Section: Hsp70 Probesmentioning
confidence: 99%
“…The highly conserved HSP70/HSC70 share approximately 90% identical sequences in the N-terminus nucleotide binding domain (NBD), but not in the C-terminus substrate binding domain (SBD)20. The affinity of SBD to substrate is strictly regulated by NBD through conformational changes induced by the hydrolysis of ATP to ADP21. The ADP-binding state exhibits a higher affinity to substrate than the ATP-binding state21.…”
mentioning
confidence: 99%
“…The affinity of SBD to substrate is strictly regulated by NBD through conformational changes induced by the hydrolysis of ATP to ADP21. The ADP-binding state exhibits a higher affinity to substrate than the ATP-binding state21. Modulating the switch between the ATP- and ADP-binding states controls the chaperone function of HSP70/HSC7021.…”
mentioning
confidence: 99%
See 1 more Smart Citation